Annotated Translation of Nights in Rodanthe by Nicholas Sparks - Ayu Bandu Retnomurti (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2016)
Translators always faced difficulties in translating. In order to manage, the translator would need to use strategies to produce effective and natural translation. In this study, the researcher was to find out the difficulties or problems and the strategies in the process of translation from English into Indonesian from the text in a novel titled Nights in Rodanthe by Nicholas Sparks. The researcher was to annotate the words, phrases, clauses, and sentences that she has translated. This area above, namely annotated translation from English into Indonesian, was chosen by the researcher in order to widen her experience in translation which was in line with her study and to detect the problems emerging during the process of translation. The research result was that the translator found some difficult problems in translation such as Lexical, Grammatical, Communication and Cultural problems in translating the words, phrases, clauses and sentences. In order that the message of the SL text could be accurately translated into the acceptable TL equivalence, she did not merely or literally translate them by retaining the forms remaining the same way as the TL text. And to reach the acceptability of the TL equivalence, certain annotated procedures of translation were required.Keywords: Annotated translation, Lexical, Grammatical, Communication and Cultural problems in translating